Analisis Komunikasi Publik Pejabat PTSP dalam Meningkatkan Kualitas Layanan di Pemerintah Kabupaten Labuhanbatu Selatan - Harahap, Jam’ah; Ginting, Rahmanita; Saleh, Arifin (Mahesa Research Center, 2024)
This study aims to analyze the public communication process of One-Stop Integrated Service officials to the public in improving the quality of services in the South Labuhanbatu Regency Government and analyze the obstacles to the public communication process of One-Stop Integrated Service officials to the public in improving the quality of services in the South Labuhanbatu Regency Government. The theories used are the theory of public communication, public services, and service quality. This research method is qualitative. The informants in this study are the Head of Service, Secretary, Service Officer, and the community of South Labuhanbatu Regency. Data analysis techniques use data reduction, data presentation, and conclusion drawing or conclusion verification. This study concludes that public communication by PTSP in improving service quality has been effective with the selection of the right media, such as social media, to facilitate the issuance of permits. The main obstacle occurs due to the lack of public attention to the information submitted according to the SOP.